Frequency and determinants of technical procedures in French general practice: a cross-sectional study - Victor Pointis; Henri Panjo; Anne-Marie Schott; Laurent Letrilliart (James Cook University, 2023)
Introduction: Technical skills have many areas of application in general practice and are a dimension of medical competence. Several studies have attempted to describe the technical procedures performed in general practice but most had limitations in the data collection process, the scope of the procedures addressed, or the healthcare actors involved. No French comparable data have been published. The aim of the present study was therefore to describe the frequency and type of technical procedures in French general practice, and to assess their determinants, in particular rurality. Methods: The present study was ancillary to the ECOGEN (Eléments de la COnsultation en médecine GENérale) study, which was an observational cross-sectional, multicentre, nationwide study conducted in 128 French general practices. Data were collected on 20 613 patient-GP encounters, including the characteristics of GPs and encounters, as well as the health problems managed during the encounter and their associated processes of care; the latter two variables were coded according to the International Classification of Primary Care classification. The GPs' practice location was first classified as rural area, urban cluster, or urban area; the former two categories were combined for analysis. The various technical procedures were classified according to the framework of the International Classification of Process in Primary Care. The frequency of each technical procedure was compared according to GP practice location. The dependent variable analysed was the performance of at least one technical procedure per each health problem managed. Bivariate analysis was performed for all independent variables followed by multivariate analysis for key variables, using a hierarchical model including three levels: the physician, the encounter, the health problem managed. Results: The data included 2202 technical procedures performed. At least one technical procedure was performed in 9.9% of encounters and for 4.6% of health problems managed. The two most frequent groups of technical procedures performed were injections (44.2% of all procedures) and clinical laboratory procedures (17.0%). The following procedures were more often performed by GPs practicing in a rural area or an urban cluster than those practicing in an urban area: injection of joints, bursae, tendons and tendon sheaths (4.1% v 1.2% of all procedures), manipulation and osteopathy (10.3% v 0.4%), excision/biopsy of superficial lesions (1.7% v 0.5%), and cryotherapy (1.7% v 0.3%). Conversely, the following procedures were more often performed by GPs practicing in urban areas: vaccine injection (46.6% v 32.1%), point-of-care testing for group A streptococci (11.8% v 7.6%), and ECG (7.6% v 4.3%). GPs practicing in a rural area or an urban cluster performed more often technical procedures than those practising in an urban area (odds ratio=1.31, 95% confidence interval 1.04-1.65), according to the multivariate model. Conclusion: Technical procedures were more frequently performed and more complex when they were performed in French rural and urban cluster areas. More studies are required to assess patients' needs regarding technical procedures.